Combined resection of the hepatic artery without reconstruction in pancreaticoduodenectomy: a case report of pancreatic cancer with an aberrant hepatic artery - Tadao Kuribara; Tatsuo Ichikawa; Kiyoshi Osa; Takeshi Inoue; Satoshi Ono; Kozo Asanuma; Shiori Kaneko; Takayuki Sano; Itaru Shigeyoshi; Kouta Matsubara; Naoko Irie; Akira Iai; et al. (Surgical Case Reports)
Abstract Background Pancreaticoduodenectomy (PD) is rarely performed for pancreatic cancer with hepatic arterial invasion owing to its poor prognosis and high surgical risks. Although there has been a recent increase in the reports of PD combined with hepatic arterial resection due to improvements in disease prognosis and operative safety, PD with major arterial resection and reconstruction is still considered a challenging treatment. Case presentation A 61-year-old man with back pain was diagnosed with pancreatic head and body cancer. Although distant metastasis was not confirmed, the tumor had extensively invaded the hepatic artery; therefore, we diagnosed the patient with locally advanced unresectable pancreatic cancer. After gemcitabine plus nab-paclitaxel (GnP) therapy, the tumor considerably decreased in size from 35 to 20 mm. Magnetic resonance imaging revealed a gap between the tumor and the hepatic artery. Tumor marker levels returned to their normal range, and we decided to perform conversion surgery. In this case, an artery of liver segment 2 (A2) had branched from the left gastric artery; therefore, we decided to preserve A2 and perform PD combined with hepatic arterial resection without reconstruction. After four cycles of GnP therapy, we performed hepatic arterial embolization to prevent postoperative ischemic complications prior to surgery. Immediately after embolization, collateral arterial blood flow to the liver was observed. Operation was performed 19 days after embolization. Although there was a temporary increase in liver enzyme levels and an ischemic region was found near the surface of segment 8 of the liver after surgery, no liver abscess developed. The postoperative course was uneventful, and S-1 was administered for a year as adjuvant chemotherapy. The patient is currently alive without any ischemic liver events and cholangitis and has not experienced recurrence in the past 4 years since the surgery. Conclusions In PD for pancreatic cancer with hepatic arterial invasion, if a part of the hepatic artery is aberrant and can be preserved, combined resection of the common and proper hepatic artery without reconstruction might be feasible for both curability and safety.